Pengaruh Fasilitas Dan Kualitas Pelayanan Terhadap Keputusan Menginap Di Hotel RedDoorz syariah near GOR Panatayuda Karawang - Didit Ramadhan Suhendra; Cecep Hermana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research was triggered by the growth rate of hotels in Falkirk high, Each Hotel also various facilities to increase the number of visitors. this will certainly affect the amount of visitors or tourists that will be st aying because of the many competitors in the city of karachi. service providers the hotel to set up the best strategy the best to attract tourists to stay, because with the advent of new Hotels travelers are becoming increasingly have a lot of choice. Hotel RedDoorz syariah near GOR Panatayuda is one that is affected by the number of competitors in the years that the more advanced and also the city of karachi which is increasingly visited by tourists. The problem in this research is what factors affect the decision of tourists to stay at Hotel RedDoorz syariah near GOR Panatayuda Karawang. Specifically focused on three variables, namely the Facilities, Quality of Services, And the Decision of Staying. The purpose of this research is to study the influence of three variables in influencing the decision of stay of tourists in the Hotel RedDoorz syariah near GOR Panatayuda Karawang. The number of samples in this study amounted to 100 respondents. The data analysis technique used is Path Analysis. Keywords : Facilities, Quality of Service, the Decision of the Stay